Capital Market Education Effect (Studi Kasus GI BEI Unipdu Jombang ) - Susilawati, Ririn; Jihad, Zahrul (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
Education has an influence in changing the attitude of someone in deciding something. Therefore, the success of the education applied to provide knowledge of the capital market conducted by GI BEI Unipdu Jombang has a very significant effect on the development of galleries and increasing knowledge of capital markets in the lines of academics and students. To respond to the impact of education in the Jombang GI BEI Unipdu, qualitative descriptive methods were used. the results revealed after the BEI GI education Experiencing an increase in Unipdu GI IDX investors from 2015 as many as 222 students, 2016 as many as 95 students and 2015 as many as 169 students and giving achievements in the Yuk Nabung Saham competition sent by the Indonesia Stock Exchange.